PERAN KEPUASAN PELANGGAN MEMEDIASI HARGA DAN LOYALITAS PELANGGAN - Wulandari, Hesti; Rahyuda, I Ketut (E-Jurnal Manajemen, 2016)
The purpose of this study was to determine the mediating role of customer satisfaction in explaining the effect of price on customer loyalty Blue Band.Penelitian brand margarine products was conducted in Denpasar, because people who consume margarine in Denpasar is very easy to find because margarine is very easy to obtain in various mini market , super market and store baking ingredients. The number of samples taken are as many as 100 respondents, using the technique of non-probability sampling with purposive sampling method. Data collected through questionnaires. The data analysis technique used in this study is the technique of path analysis (path analysis) which is an extension of the multiple linear regression analysis that is useful to assess causal relationships between variables are then issued in the form of SPSS software for windows.Hasil this study shows that the effect on customer satisfaction mediate significant positive relationship between the price effect of customer loyalty products Blue Band margarine brand in Denpasar.
Keywords: Price, Customer Satisfaction, Customer Loyalty